Il palazzo enciclopedico : la Biennale di Venezia, 55. Espozione Internazionale d'Arte. - Gioni, Massimiliano; Bell, Natalie; Bolzoni, Lina; Burnett, D. Graham; Connor, Steven; Critchley, Simon; Dillon, Brian; Galison, Peter; Grafton, Anthony; Hollywood, Amy; Kafka, Ben; Krajewski, Markus; et al. (Venice : Marsilio Editori, 2013)
af Klint, Hilma ; Altfest, Ellen ; Althamer, Pawel; Ames, Levi, Fisher ; Ancarani, Yuri ; Andre, Carl ; Aran, Uri ; Arslan, Yüksel ; Atkins, Ed ; Auriti, MArino ; Baj, Enrico ; Bakharev, Nikolay ; Barlow, Phyllida; Balka, Miroslaw ; et al.
Biennale di Venezia, Venice, 01.06.2013 - 24.11.2013
kunstcatalogus